STAT6 is a useful immunohistochemical adjunct for the diagnosis of solitary fibrous tumour - Amizatul Aini S; Nur Maya Sabrina TL; Muhamad Fakhri MS; Noraini MD; Reena Rahayu Md Zain (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Solitary fibrous tumour (SFT) is a fibrotic neoplasm, also previously designated as hemangiopericytoma. STAT6 is a protein for signal tranducers and activators of transcription (STAT) family which is involved in immune function and early cell growth. Oncogenic alteration of STAT6 plays an important role for specific driver for tumour genesis of solitary fibrous tumour via NAB2-STAT6 fusion gene. The aim of the study was to compare and evaluate STAT6 expression between SFT and other soft tissue histological mimics. We evaluated a total of 30 cases material formalin fixed paraffin embedded tissue block previously diagnosed SFT cases (n=14) and soft tissue tumours mimic cases (n=16) over period of 15 years. Fourteen SFT cases (100%) showed nuclear expression of STAT6, which was diffuse and intense. All other tumour types were negative for STAT6, except for one case of dedifferentiated liposarcoma, one gastrointestinal stromal tumour and one spindle cell lipoma, which showed weak non-specific cytoplasmic staining. Nuclear STAT6 expression is useful and reliable as adjunctive marker for solitary fibrous tumour when the diagnosis is inconclusive by conventional methods.